Binary Superlattices from Mo132 Polyoxometalates and Maghemite Nanocrystals: Long‐Range Ordering and Fine‐Tuning of Dipole Interactions. Issue 2 (18th November 2015) - Breitwieser, Romain; Auvray, Thomas; Volatron, Florence; Salzemann, Caroline; Ngo, Anh‐Tu; Albouy, Pierre‐Antoine; Proust, Anna; Petit, Christophe
Abstract : In the present article, the successful coassembly of spherical 6.2 nm maghemite (γ‐Fe2 O3 ) nanocrystals and giant polyoxometalates (POMs) such as 2.9 nm Mo132 is demonstrated. To do so, colloidal solutions of oleic acid‐capped γ‐Fe2 O3 and long‐chain alkylammonium‐encapsulated Mo132 dispersed in chloroform are mixed together and supported self‐organized binary superlattices are obtained upon the solvent evaporation on immersed substrates. Both electronic microscopy and small angles X‐ray scattering data reveal an AB‐type structure and an enhanced structuration of the magnetic nanocrystals (MNCs) assembly with POMs in octahedral interstices. Therefore, Mo132 acts as an efficient binder constituent for improving the nanocrystals ordering in 3D films. Interestingly, in the case of didodecyldimethylammonium (C12 )‐encapsulated POMs, the long‐range ordered binary assemblies are obtained while preserving the nanocrystals magnetic properties due to weak POMs–MNCs interactions. On the other hand, POMs of larger effective diameter can be employed as spacer blocks for MNCs as shown by using Mo132 capped with dioctadecyldimethylammonium (C18 ) displaying longer chains. In that case, it is shown that POMs can also be used for fine‐tuning the dipolar interactions in γ‐Fe2 O3 nanocrystal assemblies. Abstract : The successful coassembly of Mo132 polyoxometalates (POMs) and γ‐Fe2 O3 magnetic nanocrystals (MNCs) is demonstrated. The POMs inserted in octahedral γ‐Fe2 O3 interstices act as binder constituents for the MNCs, leading to a long‐range ordering. Depending on the POM size, such a structuring effect either preserves the magnetic properties of γ‐Fe2 O3 or results in a fine tuning of their dipolar interactions.